National networking in rare diseases and reduction of cardiac burden in thalassemia major. (15th December 2021) - Pepe, Alessia; Pistoia, Laura; Gamberini, Maria Rita; Cuccia, Liana; Lisi, Roberto; Cecinati, Valerio; Maggio, Aurelio; Sorrentino, Francesco; Filosa, Aldo; Rosso, Rosamaria; Messina, Giuseppe; Missere, Massimiliano; et al.
Abstract: Aims: A tailored chelation therapy guided by magnetic resonance imaging (MRI) is a strategy to improve the prognosis in iron-loaded patients, in many cases still hampered by limited MRI availability. In order to address this issue, the Myocardial Iron Overload in Thalassemia (MIOT) network was established in Italy and we aimed to describe the impact of 10-year activity of this network on cardiac burden in thalassemia major (TM). Methods and results: Within the MIOT network, 1746 TM patients (911 females; mean age 31.2 ± 9.1 years) were consecutively enrolled and prospectively followed by 70 thalassemia and 10 MRI centres. Patients were scanned using a multiparametric approach for assessing myocardial iron overload (MIO), biventricular function, and myocardial fibrosis. At the last MRI scan, a significant increase in global heart T2* values and a significantly higher frequency of patients with no MIO (all segmental T2* ≥20 ms) were detected, with a concordant improvement in biventricular function, particularly in patients with baseline global heart T2* <20 ms. Forty-seven percentage of patients changed the chelation regimen based on MRI. The frequency of heart failure (HF) significantly decreased after baseline MRI from 3.5 to 0.8% ( P < 0.0001). Forty-six patients died during the study, and HF accounted for 34.8% of deaths. Conclusion: Over 10 years, continuous monitoring of cardiac iron and a tailored chelation therapy allowed MIO reduction, with consequent improvement of cardiac function and reduction of cardiac complications and mortality from MIO-related HF. A national networking for rare diseases therefore proved effective in improving the care and reducing cardiac outcomes of TM patients. Structured Graphical Abstract: